3‐5: Late‐News Paper: Visual Fatigue Reducing 3D Glasses by Extending Depth of Field of Eyes. Issue 1 (29th May 2019) - Yamaguchi, Yuta; Ono, Takumi; Miyajima, Yasushi; Kato, Kazutoshi; Takaki, Yasuhiro
Abstract : This work proposes three‐dimensional (3D) glasses, constructed from a combination of phase plates and conventional 3D glasses, which can extend the depth of field of eyes and reduce visual fatigue caused by the vergence–accommodation conflict. A subjective evaluation validated the effectiveness of the proposed technique.